Collective stimulated Brillouin scattering with shared ion acoustic wave under the action of two overlapping laser beams. (12th November 2021) - Qiu, Jie; Hao, Liang; Cao, Lihua; Zou, Shiyang
Abstract: The overlapping of multiple beams is common in inertial confinement fusion (ICF), making the collective stimulated Brillouin scattering (SBS) with shared ion acoustic wave (IAW) potentially important because of the effectively larger laser intensities to drive the instability. In this work, based on a linear kinetic model, an exact analytic solution for the convective amplification of collective SBS with shared IAW stimulated by two overlapped beams is presented. From this solution, effects of the wavelength difference, crossing angle, polarization states, and finite beam overlapping volume of the two laser beams on the collective SBS modes with shared IAW are studied. It is found that a wavelength difference of several nanometers between the laser beams has negligible effects, except for a very small crossing angle about one degree. However, the crossing angle, beam polarization states, and finite beam overlapping volume can have significant influences. Furthermore, the out-of-plane modes, in which the wavevectors of daughter waves lie in different planes from the two overlapped beams, are found to be important for certain polarization states and crossing angles of the laser beams. This work is helpful to comprehend and estimate the collective SBS with shared IAW in ICF experiments.